Problems of Indonesian Teachers in Online Learning at SMP Negeri 1 Tamalatea, Jeneponto Regency in Pandemic Time - Muhammad Luthfi Haeruddin; Usman Usman (HUMAN: South Asian Journal of Social Studies, 2022)
This research aims to; (1) Describe the problems of Indonesian language teachers in planning online learning at SMP Negeri 1 Tamalatea, Jeneponto Regency during the pandemic; (2) Describe the problems of Indonesian language teachers in implementing online learning at SMP Negeri 1 Tamalatea, Jeneponto Regency during the pandemic; and (3) Describe the problems of Indonesian language teachers in online learning assessment at SMP Negeri 1 Tamalatea, Jeneponto Regency during the pandemic. This research is a qualitative descriptive study. The data source used is the Indonesian language teacher at SMP Negeri 1 Tamalatea. Data collection is done by: (1) observation; (2) interviews; and (3) documentation. Data analysis techniques were carried out by: (1) data reduction; (2) data presentation and; (3) drawing conclusions/verification. The results of this study resulted in a description of the teacher's problems in online learning, especially on: (1) the teacher's problem in planning online learning is the difficulty of accommodating or fulfilling the elements in the preparation of a good and correct lesson plan; (2) the problems of teachers in the implementation of online learning are teachers having difficulty managing and controlling online learning, teachers having difficulty implementing online learning because of the unpreparedness of facilities and infrastructure to support implementation, teachers having difficulty adapting to technology; and (3) the problem with teachers in online learning assessment is that teachers have difficulty in assessing student assignments, and it is difficult to carry out several types of assessments and assignments